Factors Associated with under nutrition among 6-59 Months Old Children in Rishikesh, Uttarakhand - Rehan, Abu; Kishore, Surekha; Singh, Mahendra; Jain, Bhavna; Parveen, Rukhsar (National Journal of Community Medicine, 2020)
Context: Under nutrition has long been a major public health concern in developing country like India as a leading cause of child morbidity and mortality. The study was aimed to assess the malnutrition and factors associated with it. The study was conducted to assess under nutrition in under five children and various associated factors affecting it. Methodology A community based cross sectional study was conducted among 400 under five children of rural and urban Rishikesh. Multistage sampling method was used to select the areas and systematic random sampling was used to select households. A predesigned, pre tested & semi structured questionnaire was used to collect information on various associated factors and status of under nutrition in study participants. Data was entered into excel sheets and analyzed using SPSS utilizing appropriate statistical test. Results: The prevalence of underweight was 37.3%, stunting was 43.3% and wasting was 24.5% respectively. Socio-demographic factors, child birth weight and birth order, hand washing practice by mother and common morbidity emerged as significant predictors of under nutrition. Conclusion: The burden of common morbidities and prevalence of malnutrition among under-five children in this community is very high. Our policies should aim to improve child health nutrition and growth.